Detection of Salmonella spp. Related Co-Infections Among Children with Diarrheal Diseases in Guangzhou, China - Mai Q; Luo Y; Ye R; Jiang Y; Qin Y; Guo J; Lai W; Wu Y; Luo M (Infection and Drug Resistance)
Qiongdan Mai,* Yasha Luo,* Ruoting Ye, Yongyao Jiang, Yanting Qin, Junfei Guo, Weiming Lai, Yongbing Wu, Mingyong Luo Department of Clinical Laboratory, Guangdong Women and Children Hospital, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingyong Luo, Department of Clinical Laboratory, Guangdong Women and Children Hospital, NO. 521 Xingnan Road, Panyu District, Guangzhou, People’s Republic of China, Tel +86-15920356428, Email luo-my@163.comBackground: Diarrheal diseases caused by gastrointestinal pathogens contribute to the high morbidity and mortality in children worldwide. Salmonella infection is one of the leading causes of diarrhea, especially in children under 5 years of age. This study aimed to assess the prevalence of Salmonella infection and its co-infection patterns in relation to clinical symptoms.Methods: A total of 430 stool samples of children with diarrheal diseases were collected from Guangdong Women and Children’s Hospital during January 2022 to December 2023 and used for detection. BioFire FilmArray Gastrointestinal (GI) Panel is an efficient and sensitive method used to assess infections caused by enteric pathogens simultaneously based on multiplex polymerase chain reaction (PCR) technologies.Results: Salmonella spp. was classified as the predominant pathogen in all stool specimens, with an overall positivity rate of 36.74% (158/430), of which 35.44% (56/158) were identified as Salmonella single infection. For Salmonella-related bacterial co-infection pattern, Salmonella and enteropathogenic Escherichia coli combinations accounted for 12.66% (20/158) of Salmonella-related bacterial co-infection patterns, and Salmonella plus Clostridium difficile was found in 8.86% (14/158). For Salmonella-viral co-infection pattern, the most prevalent combination was Salmonella and adenovirus (6.33%, 10/158). Notably, the proportion of mucus stools recorded in Salmonella plus C. difficile infections was statistically higher than that in single Salmonella infections (P < 0.05).Conclusion: This study provides a comprehensive understanding of the nature of Salmonella spp. co-infections in diarrheal diseases, and the possibility of clinical symptoms and enhanced treatments.Keywords: enteric pathogens, gastrointestinal infection, diarrhea, FilmArray